Cultura ambiental y su relación con el incremento de la generación de residuos sólidos en el Puerto Garcilazo Yurimaguas Loreto 2018 - Bustamante Barbaran, Marcia Elena (2023)
The present investigation work was developed in the city of Yurimaguas in the Port Garcilazo, the objective was to determine the relationship between the environmental culture of the residents and its effect in the increment and generation of solid residuals, the study for its nature had a quantitative focus, based on the scientific method whose results were measured, previous gathering of data and respective statistical analysis. The design was not of type experimental, descriptive, relacional with statistical bivariada. The population was all the families seated in the area of the Port (31 families), because this is a place for where a high percentage of products of bread enters to take that the city of Yurimaguas consumes, therefore, the commercialization aspects and the same life in general are very dynamic the one that causes generation of solid residuals. For the prosecution of the information the statistical package SPSS was used 24.0. and I use of the calculation leaf Excel, the data were presented through charts and graphic, being reached the following conclusions: The disposition exists in the population of participating in a program on Environmental Education, for an appropriate handling and disposition of its solid residuals (83,87%); it doesn't exist the equipment and schedule appropriate 858,06%) for an I pick up efficient of the solid residuals since the car recolector allows to fall the residuals during its journey (6,45%) and it doesn't sometimes happen ((9,68%); The problems of health can also be due for an inadequate handling of the solid residuals (83,87%) which contaminate the underground waters of the river Huallaga that goes by the Port, as well as to a bad final disposition that which causes air contamination producing nauseous scents and he/she also brings presence of many animals as rats, dogs, gallinazos, etc. which affect the landscape and the residents' health.